2012
DOI: 10.1007/s11764-011-0212-8
|View full text |Cite
|
Sign up to set email alerts
|

Employment experience of cancer survivors 2 years post-diagnosis in the Study of Cancer Survivors-I

Abstract: Being aware that some working cancer survivors may have negative work-related experiences and/or may not maintain full employment in later survivorship years may enable cancer survivors and employers to improve survivors' experiences at work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The literature search initially identified 8979 articles, with the majority retrieved by Medline. After removing duplicates, and exclusion on title and abstract, a total of 64 were retrieved for full text screening, of which 30 met the inclusion criteria . Table provides an overview of the main characteristics of these 30 articles, which described 25 studies, and involved a total of 32 027 participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search initially identified 8979 articles, with the majority retrieved by Medline. After removing duplicates, and exclusion on title and abstract, a total of 64 were retrieved for full text screening, of which 30 met the inclusion criteria . Table provides an overview of the main characteristics of these 30 articles, which described 25 studies, and involved a total of 32 027 participants.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 studies reported quantitative results, of which three described mainly physical problems , such as poor health status, functional limitations, chronic conditions, and arm pain/motion limitations, to influence work; six mainly described psychosocial problems , such as depressive symptoms, fatigue, exhaustion, and cognitive limitations, to affect work ability; and eleven described both physical and psychosocial problems , such as the aforementioned problems, but also lack of energy, nausea, hot flashes, coping issues, and the inability to perform physical/cognitive tasks, to influence functioning at work. In Table , a detailed and comprehensive overview of all results from these quantitative studies is given.…”
Section: Resultsmentioning
confidence: 99%
“…In studies where unemployment is included as an independent outcome, the extent of unemployment differs from 4% to 20% depending on country of origin and structure of the included population [7,9,2123]. Higher age, deteriorating physical and mental health, negative work-related experiences and low socioeconomic were significant risk factor for unemployment [9].…”
Section: Discussionmentioning
confidence: 99%
“…Many cancer survivors face the need for schedule changes, a decrease in work hours and wages, and a decline in work ability (Mehnert, 2011). Approximately 62% of survivors in the American Cancer Society Study of Cancer Survivors reported one or more negative work-related outcomes within two years of diagnosis (Yu, Ferrucci, & McCorkle, 2012).…”
Section: Introductionmentioning
confidence: 99%